Soil Stabilization Using Rice Husk Ash and Coir Fibre (International Journal of Innovative Research in Engineering & Management, 2022)
Soil stabilization is major problem for  construction and experimental purposes. Now a days used  practical work greatly explains the suitable characters of  the locally available Rice Husk Ash (RHA) to be used in the local construction industry in a way to minimize the  amount of waste Released in environment causing issues  to nature to the environment causing environmental pollution. The soil stabilization methods used in present  are very costly because of costly available stabilizing  materials like, cement, lime, etc. The cost of  stabilization may be minimized by replacing a good proportion of stabilizing agent using RHA. It will  minimize the environmental hazards also. Soil sample  taken for the study is clay with high plasticity (CH) that  requires stabilization. The soil is stabilized using  additives rice husk ash and a small amount of coir fibre.  Various results are made that shows changes in Maximum dry density (MDD), Optimum moisture  content (OMC). California bearing ratio (CBR) and  Unconfined compressive stress (UCS). The results  obtained in the present study show that the increase in  RHA content increases the OMC but decreases the MDD.  Also, the CBR value and UCS of soil are considerably  improved with the RHA content. From the observation of  maximum improvement in strength, 10% RHA content  with 6% coir fibre is recommended as optimum amount for practical purposes.
Keywords: Soil stabilization; Rice Husk Ash; fibre of coir; Index properties; Optimum Moisture Content; Unconfined Compressive Strength; Bearing capacity